Stakeholder Relevance for Reporting: Explanatory Factors of Carbon Disclosure. (March 2016) - Guenther, Edeltraud; Guenther, Thomas; Schiemann, Frank; Weber, Gabriel
Although stakeholder theory is widely accepted in environmental disclosure research, empirical evidence about the role of stakeholders in firms' disclosure is still scarce. The authors address this issue for a setting of carbon disclosure. Our international sample comprises the Carbon Disclosure Project (CDP) Global 500, S&P 500, and FTSE 350 reports from 2008 to 2011, resulting in a total of 1, 120 firms with 3, 631 firm-year observations. The authors apply Tobit regressions to analyze the relationship between carbon disclosure and the relevance of the following stakeholder groups: government, general public, media, employees, and customers. Our results confirm that in addition to carbon performance, all stakeholders are associated with carbon disclosure. Only one stakeholder group (government) acts as a moderator for the relationship between carbon performance and carbon disclosure. Furthermore, the authors find that carbon performance but not the affiliation to a carbon-intensive industry acts as a moderator between stakeholder relevance and carbon disclosure.